The effect of piscivorous fish stocking on the planktivorous fish, zooplankton, and phytoplankton communities of 31 southeastern Ontario lakes. - Wilson, Andrew Stewart. (University of Ottawa (Canada), 1996)
Over the past 15 years a great deal of literature has been generated in an attempt to understand the regulation of trophic level biomass and size structure in aquatic systems. I tested the hypotheses that the among-lake variability in biomass and size structure of planktivorous fish, zooplankton, and phytoplankton communities depends on: (1) resource availability (bottom-up processes); (2) piscivorous sport fish stocking (top-down processes); and (3) the particular species of piscivorous sport fish stocked. We sampled 31 lakes in southeastern Ontario over the summers of 1993 and 1994 to obtain indices of abundance, biomass, and size structure of the planktivorous fish, zooplankton, and phytoplankton communities. Seven of the lakes were not stocked and the remaining 24 had stocking intensities ranging from 30 to 1500 individuals stocked per hectare over the 6 years prior to sampling. For both bottom-up and top-down analyses, trophic interactions were strongest at the base of the food web and weakened at higher levels, becoming non-significant thereafter. From these results I conclude that: (1) piscivorous sport fish stocking as a whole (at least at the magnitude examined here) had no effect on planktivorous fish, zooplankton, and phytoplankton biomass or size structure; (2) rainbow trout (Oncorhynchus mykiss) stocked lakes differ at the zooplankton and phytoplankton level from lakes stocked with other species of piscivore; (3) trophic interactions are most evident at the base of the food web (at the zooplankton and phytoplankton level); and (4) resource control (especially total phosphorus) of biomass and size structure in aquatic communities is much more important than consumer control, and it is limited to the phytoplankton and zooplankton. Our results suggest that stocking with piscivorous fish (as practised for sport fishing purposes) does not effectively manipulate plankton abundance. (Abstract shortened by UMI.)
Keywords: Biology, Ecology.